Institutional Readiness for Indonesia’s Criminal Procedure Reform Under RUU KUHP - Abdul Basit Dihqan (Advances in Public Law and Policy, 2026)
Purpose: This study aims to analyze the readiness of Indonesia’s judicial institutions–courts, prosecutors, and police–in implementing the Rancangan Undang-Undang Kitab Undang-Undang Hukum Pidana (RUU KUHP), which has been enacted as UU No. 1 Tahun 2023 concerning the Kitab Undang-Undang Hukum Pidana, as well as the upcoming Draft Kitab Undang-Undang Hukum Acara Pidana (RUU KUHAP 2025), which will take effect on January 2, 2026. Research Methodology: This study uses a qualitative legal approach in Indonesia based on the analysis of UU No. 1 Tahun 2023, the Draft RUU KUHAP 2025, and relevant government reports. A descriptive analysis was conducted to assess institutional coordination and readiness within the new legal framework. Results: The findings revealed uneven institutional readiness. Prosecutors showed moderate preparedness owing to internal regulatory adjustments and structural reforms. In contrast, courts and police institutions face challenges related to inter-agency coordination, human resource capacity, and digital infrastructure. Differences in procedural interpretation may also create implementation gaps in the field. Conclusions: Although the Rancangan Undang-Undang Kitab Undang-Undang Hukum Pidana (RUU KUHP), now enacted as UU No. 1 Tahun 2023, represents a major transformation of Indonesia’s criminal justice system, its effective implementation depends on stronger institutional coordination, capacity building, and technological support. Limitations: This study was limited by restricted access to detailed internal institutional data. Contributions: This research contributes to the study of criminal law reform and institutional governance by highlighting the importance of organizational readiness in ensuring the successful implementation of UU No. 1 Tahun 2023 concerning the Kitab Undang-Undang Hukum Pidana in Indonesia.